Combined mean value engine model and crank angle resolved in-cylinder modeling with NOx emissions model for real-time Diesel engine simulations at high engine speed. (August 2015) - Maroteaux, Fadila; Saad, Charbel
Abstract: This study is an extension of a previous MVEM (Mean Value Engine Models) and in-cylinder single zone model dedicated for HIL (Hardware In the Loop) applications. The in-cylinder single zone model has been modified into a two zone model for the combustion phase. Thus a Zeldovich extended mechanism has been used to simulate engine out NOx level. The entire model works as a combination of an MVEM approach for the engine periphery, of a single zone in-cylinder model for the intake-compression-exhaust strokes and of a two zone model for the combustion process. The combustion process is modeled through a double Wiebe equations developed previously. The proposed two zone and NOx models have been first coded using Matlab/Simulink software before its implementation on a HIL test bench. The in-cylinder extended model has required a quad Core RTPC to reach the step time of real time simulations where one core has been dedicated to the combustion process. The comparison of measured and calculated in-cylinder pressure and NOx emissions has shown a good accuracy. The mean relative error between the calculated and the measured indicated mean effective pressure is for example lower than 2%. Highlights: Two zone in-cylinder model for Diesel engine. Combined single zone model and two zone model. Engine-out NOx level modeled through the extended Zeldovich mechanism. Hybrid modeling approaches for HIL test bench.